![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
P= 125x^3-8y^3
=5^3x^3-2^3y^3
=(5x)^3-(2y)^3
=(5x-2y)(25x^2+10xy+4y^2)
P=4x(x-2y)+8y(2y-x)
=4x(x-2y)-8y(x-2y)
=(4x-8y)(x-2y)
=4(x-2y)(x-2y)
=4(x-2y)^2
(2x+1)^2-(x-1)^2=(2x+1-x+1)(2x+1+x-1)
=(x+2)3x
K NHA!
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(x-2y+x^2-4y^2=\left(x-2y\right)+\left(x-2y\right)\left(x+2y\right)=\left(x-2y\right)\left(1+x+2y\right)\)
b, \(x^2-4x^2y^2+y^2+2xy=\left(x+y\right)^2-\left(2xy\right)^2\)
\(=\left(x+y-2xy\right)\left(x+y+2xy\right)\)
c, \(x^6-x^4+2x^3+2x^2=x^6+2x^3+1-x^4+2x^2-1\)
\(=\left(x^3+1\right)^2-\left(x^2-1\right)^2=\left(x^3-x^2+2\right)\left(x^3+x^2\right)\)
\(=x^2\left(x+1\right)\left(x^3-x^2+2\right)\)
d, \(x^3+3x^2+3x+1-8y^3=\left(x+1\right)^3-\left(2y\right)^3=\left(x+1-2y\right)\left(x+1+2y\right)\)
a) Ta có: \(x-2y+x^2-4y^2\)
\(=\left(x-2y\right)+\left(x-2y\right)\left(x+2y\right)\)
\(=\left(x-2y\right)\left(1+x+2y\right)\)
b: Ta có: \(x^2-4x^2y^2+y^2+2xy\)
\(=\left(x+y\right)^2-\left(2xy\right)^2\)
\(=\left(x+y-2xy\right)\left(x+y+2xy\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
`a,-x^3/8 + 3/(4x^2) - 3/(2x) +1`
`=-(x^3/8 - 3/(4x^2) + 3/(2x) - 1)`
`=-(x/2 - 1)^3`
`b,x^6 - 3/(2x^{4} y) + 3/(4x^{2}y^{2}) - 1/(8y^{3})`
`=(x^3 - 1/(2y))^{3}`
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm
a) 4x - 8y
<=> 4( x - 2y )
b) 12x( x - 2y ) - 8y( x - 2y )
<=> ( 12x - 8y )( x - 2y )
<=> 4( 3x - 2y )( x - 2y )
c) 2x + 2y - x2 - xy
= 2( x + y ) - x( x + y )
= ( x + y )( 2 - x )
d) x2 - 4y2
<=> ( x - 2y )( x + 2y )
e) x3 + x2y - 4x - 4y
<=> x2( x + y ) - 4( x + y )
<=> ( x - 2 )( x + 2 )( x + y )
g) 3x2 - 6xy + 3y2 - 12x3
<=>3( x2 - 3xy + y2 - 4x3 )
# Học tốt #
a)4(x-2y)
b)(x-2y)(12x-8y)
=4(x-2y)(3x-2y)
c)2(x+y)-x(x+y)
=(2-x)(x+y)
d)(x-2y)(x+2y)
e)x2(x+y)-4(x+y)
=(x+y)(x2-4)
=(x+y)(x-2)(x+2)
g)3(x2-2xy+y2-4z3)
=3[(x-y)2-4z3]
????????????phải là 4z2chứ nhỉ.....
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
\(12xy-4x^2y+8xy^2\\ =4xy\cdot\left(3-x+2y\right)\)
b)
\(4x\cdot\left(x-2y\right)-8y\cdot\left(x-2y\right)\\ =4\cdot\left(x-2y\right)\cdot\left(x-2y\right)\\ =4\cdot\left(x-2y\right)^2\)
c)
\(25x^2\cdot\left(y-1\right)-5x^3\cdot\left(1-y\right)\\ =-25x^2\cdot\left(1-y\right)-5x^3\cdot\left(1-y\right)\\ =\left(1-y\right)\cdot\left(-25x^2-5x^3\right)\\ =5x^2\left(1-y\right)\cdot\left(-5-x\right)\)
d)
\(3x\cdot\left(a-x\right)+4a\cdot\left(a-x\right)\\ =\left(a-x\right)\cdot\left(3x+4a\right)\)
e)
\(x^3-3x^2+2\\ =x^3-x^2-2x^2+2\\ =x^2\cdot\left(x-1\right)-2\left(x^2-1\right)\\ =x^2\cdot\left(x-1\right)-2\cdot\left(x-1\right)\cdot\left(x+1\right)\\ =\left(x-1\right)\left[x^2-2\cdot\left(x+1\right)\right]\\ =\left(x-1\right)\cdot-\left(x^2+2x+1\right)\\ =\left(x-1\right)\cdot-\left(x+1\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: 2x^2y-50xy=2xy(x-25)
b: 5x^2-10x=5x(x-2)
c: 5x^3-5x=5x(x^2-1)=5x(x-1)(x+1)
d: \(x^2-xy+x=x\left(x-y+1\right)\)
e: x(x-y)-2(y-x)
=x(x-y)+2(x-y)
=(x-y)(x+2)
f: 4x^2-4xy-8y^2
=4(x^2-xy-2y^2)
=4(x^2-2xy+xy-2y^2)
=4[x(x-2y)+y(x-2y)]
=4(x-2y)(x+y)
f1: x^2ỹ-y^2+y
=(x-y)(x+y)+(x+y)
=(x+y)(x-y+1)